2015
DOI: 10.1111/acer.12847
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Binge Drinking Increases Perineuronal Nets in the Insular Cortex

Abstract: Background Alcohol exposure leads to changes in the extracellular matrix (ECM) in the brain, which profoundly impacts neuronal plasticity. Perineuronal nets (PNs) are specialized ECM structures that enclose subpopulations of neurons in the cortex. Adolescent exposure to alcohol induces long-lasting increases in the expression of PN components in the cortex in adult mice. However, it has not been determined whether binge alcohol exposure in young adults alters PNs. Here, we examined PNs and their core component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 38 publications
6
64
0
Order By: Relevance
“…Binge-like ethanol drinking in mice increases PNNs and elevates expression of CSPGs aggrecan, brevican, and phosphacan in the insula, but not anterior cingulate or primary motor cortex [91]. In the OFC, PNNs and CSPGs brevican and neurocan are elevated in adult mice exposed to alcohol during adolescence [92].…”
Section: Drug Withdrawal and Constitutive Corticostriatal Synaptic Plmentioning
confidence: 99%
“…Binge-like ethanol drinking in mice increases PNNs and elevates expression of CSPGs aggrecan, brevican, and phosphacan in the insula, but not anterior cingulate or primary motor cortex [91]. In the OFC, PNNs and CSPGs brevican and neurocan are elevated in adult mice exposed to alcohol during adolescence [92].…”
Section: Drug Withdrawal and Constitutive Corticostriatal Synaptic Plmentioning
confidence: 99%
“…Coleman and colleagues (2014) found that binge-like ethanol exposure in adolescent mice induced an increase in PNN expression in orbitofrontal cortex (OFC) when mice reached adulthood. This effect was also observed in young adult mice under similar experimental conditions (Chen et al, 2015). Furthermore, a cocaine-sensitizing regimen decreased PNN expression in the medial nucleus of the cerebellum (Vazquez-Sanroman et al, 2015a).…”
Section: The Involvement Of Pnns In Drug Addictionsupporting
confidence: 62%
“…Previous research conducted across a variety of animal species (i.e., rhesus monkey (43, 44), bison (45), dog (46), gerbil (47), guinea pig (48), zebra finch (49), rat (38), and mouse (25, 50-56)) has shown PNNs to be widely distributed in the brain. Similarly, in humans, PNNs have been found to be present in a variety of brain regions, including entorhinal cortex (28), amygdala (28, 29, 57), hippocampus (58), motor and somatosensory cortex (59), visual cortex (27) and prefrontal cortex (27), all regions (bar the visual cortex) which have been reported to be affected in schizophrenia (60).…”
Section: Characteristics Of Pnns: Molecular Heterogeneity Distributimentioning
confidence: 99%
“…Given that PNN-encapsulated neurons are prevalent throughout the limbic system (28, 29, 76) and PNNs are capable of modulating receptors (i.e., α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid, AMPA receptors) known to be integral for learning and memory (77), these structures have been considered to play an important role in memory formation (54), which may include emotional memory (51, 55) in addition to reward-related memory (50, 78). In fact, it has been reported that PNNs are involved in long-term potentiation (LTP) and long-term depression (LTD) in hippocampal slices, as these physiological events are impaired following enzymatic degradation of CSPGs, or removal of TN-R (79, 80).…”
Section: The Role Of the Pnn In The Modulation Of Cognitive Functionmentioning
confidence: 99%
See 1 more Smart Citation